Porcine Endogenous Retroviruses: Quantification of the Viral Copy Number for the Four Miniature Pig Breeds in China - Lu, Tao-feng; Sun, Bo; Yu, Tai-yong; Wu, Yan-jun; Zhou, Jie; Wu, Shu-guang (Frontiers in Microbiology, 2022)
Domestic pigs has served not only as one of the most important economy livestock but also as ideal organ-source animals owing to similarity in anatomy, physiology and organ size to humans. Howerer, the barrier of the cross-species transmission risk of porcine endogenous retrovirus (PERVs) blocked the pig-to-human xenotransplantation. PERVs are integrated into pigs' genomes and cannot be eliminated by designated or speciﬁed pathogen-free breeding. PERVs are an important biosafety issue in xenotransplantation because they can be released from normal pig cells and infect human cells in vitro under certain conditions. Screening and analyzing the presence of PERVs in pig genome will provide essential parameters for pig breed sources. In China, four miniature pig breeds, such as Guizhou miniature pig (GZ), Bama miniature pig (BM), Wuzhishan miniature pig (WZS), and Juema miniature pig (JM), were the main experimental miniature pig breeds, which were widely used. In this study, PCR was performed to amplify env-A, env-B, and env-C for all individuals from the four breeds. The results revealed that PERV env-A and env-B were detected in all individuals and the lowest ratios of PERV env-C was 17.6 % (3/17) in the GZ breed. Then, PERV pol and GAPDH were detected using the droplet digital PCR (ddPCR) method. As the reference of GAPDH copy number, the copy numbers of PERVs were at the median of 12, 16, 14, and 16 in the four miniature pig breeds (GZ, BM, WZS, and JM), respectively. Furthermore, the copy number of the PERV pol gene in many organs from the GZ breed was analyzed using ddPCR. The copy numbers of PERV pol gene were at the median of 7 copies, 8 copies, 8 copies, 11 copies, 5 copies, 6 copies, and 7 copies in heart, liver, spleen, lung, kidney, muscle, and skin, and the maximum number was 11 copies in the lung. The minimum number was 5 copies in the kidney as the reference of GAPDH. These data suggest that GZ breed has the lower PERVs copy number in the genome, and may be an ideal organ-source miniature pig breed for the study of the pig-to-human xenotransplantation.